Changing concentrations of CO, CH 4 , C 5 H 8 , CH 3 Br, CH 3 I, and dimethyl sulfide during the Southern Ocean Iron Enrichment Experiments - Wingenter, OW; Haase, KB; Strutton, P; Friederich, G; Meinardi, S; Blake, DR; Rowland, FS (Proceedings of the National Academy of Sciences, 2004)
Oceanic iron (Fe) fertilization experiments have advanced the understanding of how Fe regulates biological productivity and airsea carbon dioxide (CO 2 ) exchange. However, little is known about the production and consumption of halocarbons and other gases as a result of Fe addition. Besides metabolizing inorganic carbon, marine microorganisms produce and consume many other trace gases. Several of these gases, which individually impact global climate, stratospheric ozone concentration, or local photochemistry, have not been previously quantified during an Fe-enrichment experiment. We describe results for selected dissolved trace gases including methane (CH 4 ), isoprene (C 5 H 8 ), methyl bromide (CH 3 Br), dimethyl sulfide, and oxygen (O 2 ), which increased subsequent to Fe fertilization, and the associated decreases in concentrations of carbon monoxide (CO), methyl iodide (CH 3 I), and CO 2 observed during the Southern Ocean Iron Enrichment Experiments.